Real Exchange Rate and Consumption Fluctuations following Trade Liberalization - Kristian Jönsson (Sveriges Riksbank, 2005)
Two-sector models with traded and non-traded goods have problems accounting for the stylized fact that the real exchange rate appreciates and consumption booms for several years following trade liberalization, or exchange-rate-based stabilization programs, in small open economies. The paper studies three potential solutions to this price-consumption puzzle and evaluates their quantitative importance in calibrated simulations of Spains accession to the European Community in 1986. Extending the standard two-sector framework, the paper investigates the effects of relative productivity growth in the traded sector along the lines of Balassa-Samuelson, of time-to-build, and of habit formation in preferences. In contrast to previous studies, we find that habit formation on its own does not enable the model to account for the observed real exchange rate and consumption dynamics. The analysis shows that a calibrated version of the model augmented with all three mechanisms can account for much of the price-consumption dynamics after trade liberalization, without losing explanatory power for other real variables in the Spanish economy after 1986.
Keywords: C68; F41; 330; Non-traded goods; Balassa-Samuelsson; Time-to-build; Habit formation; Dynamic general equilibrium